FORMATION OF CARBON STEEL STRUCTURE DURING HOT PLASTIC DEFORMATION - Vakulenko, I. O.; Bolotova, D. M.; Proidak, S. V.; Askerov, H.; Cug, H.; Tchaikovska, H. O. (Science and Transport Progress, 2020)
Purpose. The main purpose of the work is to determine the peculiarities of the development of recrystallization processes of carbon steel austenite depending on the degree of hot plastic deformation and to develop proposals for improving the structural state of the metal of the railway solid-rolled wheel. Methodology. Two carbon steels of a railway wheel with a minimum and maximum carbon content of 0.55 and 0.65 % and other chemical elements within the grade composition of the steel 60 were used as research material. Samples in the form of cylinders with a diameter of 20 mm and a height of 40 mm were heated in a muffle furnace, exposed for a certain time to equalize the temperature across the cross section of the sample. After that, the samples were subjected to hot compression on Instron type test machine. The temperature interval of hot compression of the samples was 950–1100 ºС, with deformation degrees in height in the range of 10–40%. The strain rate was 10-3–10-2sec-1. A standard etching was used to detect the boundaries of the austenite grains. Structural studies were performed using Epikvant type light microscope at magnifications sufficient to determine the structure of austenite grains. The grain size of austenite was determined by the methods of quantitative metallography. Findings. In the case of hot compression of the railway wheel blank, increasing the concentration of carbon atoms only within the grade composition of the steel is sufficient to increase the average austenite grain size, which confirms the proposals to limit the carbon content in the metal of railway wheels. The formation of a certain degree of austenite structural heterogeneity at the cross section of the rim or hub of the railway wheel is due to a change in the development mechanism of recrystallization processes depending on the deformation value. Under conditions of the same degree of hot plastic deformation, the replacement of one-time compression by fractional one is accompanied by a violation of the conditions of formation of the recrystallization nucleus. As a result of the specified replacement of the scheme of hot plastic deformation we obtain reduction in the austenite grain size. Originality. Based on a study of the development of collective recrystallization processes during the hot compression of carbon steel of the railway wheel, it was determined that the increase in carbon content contributes to the austenite grain increase. After hot compression of the wheel blank, the structural inhomogeneity of austenite that occurs is determined by a change in the mechanism of recrystallization processes development. During deformations above the critical degree, the recrystallization nuclei are formed and successively grow, which leads to the structure refinement. In the case of deformations below the critical value, the growth of austenite grains occurs according to the coalescence mechanism, according to which fragments of boundaries with large disorientation angles consistently disappear. Practical value. For austenite grain refining in massive elements of solid-rolled railway wheel we offer to replace one-time hot compression by fractional one.